Hypersonic Vehicle Tracking Based on Improved Current Statistical Model - He Guangjun; Lv Hang; Li Baoquan; Li Yanbin (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
A new method of tracking the near space hypersonic vehicle is put forward. According to hypersonic vehicles’ characteristics, we improved current statistical model through online identification of the maneuvering frequency. A Monte Carlo simulation is used to analyze the performance of the method. The results show that the improved method exhibits very good tracking performance in comparison with the old method. DOI: http://dx.doi.org/10.11591/telkomnika.v11i11.2786